Improvement of Antitumor Therapies Based on Vaccines and Immune-Checkpoint Inhibitors by Counteracting Tumor-Immunostimulation - Chiarella, Paula; Vermeulen, Mónica; Montagna, Daniela R.; Vallecorsa, Pablo; Strazza, Ariel Ramiro; Meiss, Roberto P.; Bustuoabad, Oscar D.; Ruggiero, Raúl A.; Prehn, Richmond T. (Frontiers in Oncology, 2018)
Immune-checkpoint inhibitors and anti-tumor vaccines may produce both tumor-inhibitory and tumor-stimulatory effects on growing tumors depending on the stage of tumor growth at which treatment is initiated. These paradoxical results are not necessarily incompatible with current tumor immunology but they might better be explained assuming the involvement of the phenomenon of tumor-immunostimulation. This phenomenon was originally postulated on the basis that the immune response (IR) evoked in Winn tests by strongly-immunogenic chemically-induced murine tumors was not linear but biphasic, with strong IR producing inhibition and weak IR inducing stimulation of tumor growth. Herein, we extended those former observations to weakly-antigenic spontaneous murine tumors growing in pre-immunized, immune- competent and immune-depressed mice. Furthermore, we demonstrated that the interaction of specifically-immune T cells and target tumor cells at low stimulatory ratios enhanced the production of chemokines aimed to recruit macrophages at the tumor site, which, upon activation of TLR4 and p38 signaling pathways, would recruit and activate more macrophages and other inflammatory cells which would produce growth-stimulating signals leading to an accelerated tumor growth. On this basis, the paradoxical effects achieved by immunological therapies on growing tumors could be explained depending upon where the therapy-induced IR stands on the biphasic IR curve at each stage of tumor growth. At stages where tumor growth was enhanced (medium and large-sized tumors), counteraction of the tumor-immunostimulatory effect with anti-inflammatory strategies or, more efficiently, with selective inhibitors of p38 signaling pathways enabled the otherwise tumor-promoting immunological strategies to produce significant inhibition of tumor growth.